Production of Tannase enzyme from Industrial Waste to abate Environmental Pollution - Prakash, D.S.R.S.; Deedi, M.Kiran (Asian Journal of Biological and Life Sciences, 2020)
Enzymes and micro-organisms can be used for the bioconversion of biological materials into useful products. A few reports are available in the literature on the production of tannase through biotechnological routes. A novel route for the production of enzyme tannase using the principles of fermentation technology and organic chemistry. Biological degradation is adjudged as an important mechanism of organic chemical removal in natural systems, owing to its environmental compatibility and plasticity. Consequently, microbial metabolic potentials are widely exploited for a number of industrial applications including decommissioning of environmental pollutants. An important enzyme having various industrial applications is tannase (tannin acyl hydrolase). It is an extracellular enzyme falling under the hydrolase group of enzymes. Tannin acyl hydrolase (E.C.3.1.1.20) commonly called tannase, catalyzes the hydrolysis of ester and depside bonds in such hydrolysable tannins as tannic acid, thereby, releasing glucose and gallic acid. Tannase is an inducible enzyme produced only in the presence of tannic acid, or its end-product, i.e., gallic acid. The work deals with the extraction of tannins and production of tannase enzyme from Cashew testa waste by submerged fermentation using immobilized cells of mutated strain Cashew,Anacardium occdentale, is widely cultivated in India especially in coastal Andhra Pradesh. The Cashew testa after taking out the raw nuts has been thrown by cashew industries. The testa of Cashew has a long number of tannins. This disposed testa containing toxic chemicals like tannic acid from tannins causing environmental pollution by contaminating the local ground water.
Keywords: Cashew husk; Enzyme extraction.; Tannase; Tannins